Defining a “Good Death”: Exploring Veterinarians’ Perceptions of Companion Animal Euthanasia - Lori R. Kogan; Kathleen A. Cooney (Animals, 2023)
This study was designed to determine how veterinarians define a good euthanasia experience. This information is used to generate a working definition of companion animal euthanasia that aligns with animal welfare standards and pet owners’ expectations. An electronic survey distributed via veterinary-related social media (Facebook, Instagram) and listservs were completed by 249 veterinarians who perform feline and/or canine euthanasia. Our results suggest that very few veterinarians feel their veterinary school training adequately prepared them for euthanasia. When veterinarians were asked to rank a list of physiologic conditions and anatomical traits in order of euthanasia-related concerns, respiratory distress was ranked the highest, while the most concerning physical changes were reported to be indications or impressions of seizures or pain. The most commonly reported euthanasia injection technique performed by participants was intravenous administration of pentobarbital sodium (97%), and most veterinarians preferred having owners present (57%) or having no preference (38%) during euthanasia. Results suggest that veterinarians want a pain-free, anxiety-free experience for the patient, appreciate the use of sedatives before euthanasia, and feel that when available and appropriate, home euthanasia offers several benefits. This understanding of the numerous aspects involved in a good euthanasia experience can help inform the creation of an updated definition of companion animal euthanasia that strives to prioritize the welfare of the patient as well as the needs and expectations of the pet owner.